Diaminonaphthalene and guanidine as scaffolds for pi-conjugated amido ligands: Versatile supporting frameworks for transition and main group elements - Bazinet, Patrick R (University of Ottawa (Canada), 2004)
This work was launched with a desire to develop novel versatile amido ligands for transition and main group metals. Of utmost importance was building ligands capable of forming strong and robust metal-ligand interactions. Bidentate mono- and di-anionic amido ligands were targeted due to the advantageous effects of chelation. 1,8-Diaminonaphthalene (1,8-DAN) and guanidines were identified as target ligand platforms. The majority of this work deals with the preparation and use of 1,8-DAN based dianionic ligands for transition (Ta, Zn) and main group (B, Al, C, Ge, Sn) metals. The synthesis and reactivity of half-sandwich zirconium guanidinato compounds is also presented. Chapter 1 presents the fundamental concepts surrounding ligand design and presents our rationale for choosing to investigate diamidonaphthalene and guanidinate ligands. Chapter 2 discusses the synthetic routes utilized for the preparation of both classes of ligands used further in this work. Reductive alkylation was used to introduce bulky secondary alkyl groups on the 1,8-DAN frame. The preparation of a guanidine ligand tethered to a silsesquioxane is also reported. Chapter 3 presents our efforts in preparing high-valent Ta(V) complexes supported by 1,8-DAN based ligands. Prevalent in this work is the tendency for Ta alkyl groups to further react with the ligand via C-H activation forming a metallaaziridine. Chapter 4 deals with the 1,8-DAN framework's ability to stabilize singlet carbenes. This new class of N-Heterocyclic Carbene (NHC) possessing a perimidine core demonstrates spectroscopic and reactive characteristics resembling those of the more reactive imidazolidine based NHCs. Chapter 5 describes the preparation of heavier group 14 analogues of perimidine based carbenes. The solid-state structure of the stannylene analogue indicated the presence of intermolecular Sn···arene interactions which were investigated using DFT calculations. Chapter 6 investigates the Lewis basic character of carbenes and germylenes supported by diamidonaphthalene and their potential as ligands for late transition metals. Chapter 7 discusses the use of diisopropyl-1,8-DAN as a ligand for the stabilization of coordinatively unsaturated group 13 elements. Chapter 8 presents a spectroscopic and structural study of mono(cyclopentadienyl)zirconium guanidinato species. Chapter 9 summarizes the work presented in this thesis and discusses how the work reveals but a sliver of the enormous potential of diamidonaphthalene ligands. (Abstract shortened by UMI.)
Keywords: Chemistry, Inorganic.